Materializing policies for sustainable use and economy-wide management of resources: biophysical perspectives, socio-economic options and a dual approach for the European Union - Stefan Bringezu (Wuppertal Institut für Klima, Umwelt, Energie, 2006)
Policies for Sustainable Use and economy-wide Management of natural Resources (SUMR) throughout the production and consumption system are faced with environmental and socio-economic requirements and regulatory constraints. Based on empirical findings of ongoing trends of resource use, decoupling from economic growth, and transregional problem shifting, the paper outlines a potentially sustainable biophysical basis for production and consumption in the EU. It discusses the main challenges for the major resource groups, describing the specific and the common tasks with regard to biomass, fossil fuels, metals, non-metallic minerals. Adopting a medical metaphor, it suggests that policies for SUMR should follow a dual approach reflecting the long-term need for a main cure of the socio-industrial metabolism in form of a conditioning towards a more mature, resource efficient, and renewables based constitution on the one hand, and a fine tuning of selected material flows (e.g. for optimized recycling and control of hazardous compounds) on the othe hand. Both strategies are deemed complementary and necessary to reduce environmental impact and increase the utility of material use. Action required is exemplified with regard to the three pillars of SUMR, i.e. improved orientation, information and incentives.
urn:nbn:de:101:1-200910202042
Keywords: 330; Material efficiency; dematerialization; renewables; socio-industrial metabolism; resource use; environmental impacts; sustainable production & consumption; bioeconomy